Intervensi Analisis Lirik: Mengatasi Ruminasi Kognitif Remaja Akhir Perempuan dengan Lirik Lagu BTS - Ernestine Oktaviana Yuniswara; Nurul Hartini (INSAN Jurnal Psikologi dan Kesehatan Mental, 2022)
The tendency toward cognitive rumination among females in their late adolescence was increasing during the COVID-19 pandemic, which in turn may lead to the development of anxiety and depression disorders. Lyrics Analysis Intervention in group aiming to redirect thoughts and introduce more effective coping mechanisms is one of the methods in Cognitive Behavioral Therapy to overcome cognitive rumination. In this report, the characteristic shared by the intervention group members as a fan of the South Korean boy band, BTS (Bangtansonyeondan), was used as a basis of the song selection. Discussing the song "Permission to Dance" with its optimistic lyrics has provided insight into positive and effective coping strategies as a way to conduct cognitive rumination. The results of this research suggest that combining Lyrics Analysis Intervention with psychoeducation and self-monitoring task can reduce the participants' symptoms of depression, anxiety, and stress.